KARAKTERISTIK DAN KEPATUHAN WAJIB PAJAK UMKM - Ismail, Marthinus (Jurnal Ekonomis, 2024)
Fair and equitable tax management by the government brings positive psychological effects to the community. Tax management, which can be felt by the community, allows for the growth of community compliance in the field of taxation. In 2024, the compliance of corporate taxpayers (WP) in reporting the Annual Tax Return is only 67%. Therefore, this study aims to test the compliance of taxpayers from Micro, Small and Medium Enterprises (MSMEs) from the knowledge factor and tax sanctions as well as the implementation of e-SPT. The research data was obtained from the distribution of questionnaires. The population was taken from MSMEs around Parongpong District and around 30 respondents were found who could be used as a sample. The description and statistical regression obtained from the data were processed to test this study. The results of the study show that the compliance of MSME taxpayers is not significantly influenced by knowledge and tax sanctions, but the opposite applies with the implementation of e-SPT. Simultaneously, the compliance of MSME taxpayers is significantly affected by all characteristics of taxpayers